SPE Annual Technical Conference and Exhibition 1989
DOI: 10.2118/spe-19691-ms
|View full text |Cite
|
Sign up to set email alerts
|

Foam Performance Under Reservoir Conditions

Abstract: Foams that effectively reduce gas permeability were formed over a wide range of experimental conditions. The ability of selected foaming agents to form foam was evaluated in bulk foam measurements, screening core tests, and in reservoir condition core tests. Results reported show that oil usually adversely affected foam performance with higher molecular weight alkanes showing less of an adverse effect for the foaming agents tested. Foam can be effectively generated in an oil-wet porous medium but was shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Foam is generally thought to be more efficient (i.e., easier to form and more stable) in waterwet rocks than in mixed/oil-wet porous media (Farajzadeh, et al, 2012b;Rossen, 1996;Schramm et al, 1994Schramm et al, , 1996Suffridge et al, 1989). Though, findings supporting good CO 2foam performance in oil-wet medium have also been reported (Haugen et al, 2014Lescure and Claridge, 1986;Rafati and Hamidi, 2011;Romero-Zeron and Kantzas, 2007).…”
Section: Wettability/lithological Effectsmentioning
confidence: 93%
“…Foam is generally thought to be more efficient (i.e., easier to form and more stable) in waterwet rocks than in mixed/oil-wet porous media (Farajzadeh, et al, 2012b;Rossen, 1996;Schramm et al, 1994Schramm et al, , 1996Suffridge et al, 1989). Though, findings supporting good CO 2foam performance in oil-wet medium have also been reported (Haugen et al, 2014Lescure and Claridge, 1986;Rafati and Hamidi, 2011;Romero-Zeron and Kantzas, 2007).…”
Section: Wettability/lithological Effectsmentioning
confidence: 93%
“…In the high‐pressure floods, the dense state of the gas acts more like a liquid than like the gas but it does not cause any difficulty in the formation of the foam . Suffridge et al and Mannhardt et al also showed the possibility of foam formation in porous media with hydrocarbon gas under miscible conditions. It should be noted that “foams” are mainly referred to the dispersion of the gas in a liquid phase; whereas, the dispersions of a dense, liquid‐like state of the gas phase or solvent in an aqueous phase might more appropriately be called emulsions .…”
Section: Introductionmentioning
confidence: 99%
“…Foam stability can be reduced with decreasing carbon content in crude oils. It has also been observed elsewhere that a lower number alkanes are more destabilizing than higher number alkanes, because their shorter hydrocarbon chains are more easily imbibed into foam plateau borders to solubilize with surfactants leading to oil spreading and foam instability [10,[37][38][39].…”
Section: Multiple-contact Miscible Conditionsmentioning
confidence: 99%